Rabbit ∧∨ Duck - Ramos, M. (2022 PhDCS Workshop The future of Complex Systems Science, 2022)
There are things going on in the world beyond our Western eye and navel that we either don’t wish to acknowledge, to highlight, or even to comprehend. I’m ready to try to embrace any alternative views that make sense of Afghanistan’s place in this seismic shift in world affairs. Interpretations based on opposing ideological categories such as Democracy vs Autocracy, Universal values vs Relativist (or Regional) values, Freedom vs Oppression (that can be seen as new iterations of the old adage “The West vs the Rest”) are not helpful to grasp the immensity and complexity of the world beyond our mental and cultural borders. Two major blocks are being formed: one that is majorly Oceanic, and relies on seabed cable networks that link the Atlantic, the Indian Ocean and the Pacific, through which state hegemony reinforces digital spying control – I’d call it the Five-Eyes plus One (the One being Sweden, that sits on top of the heaviest flux of cable data) –, and another hegemon that stretches throughout the immense continent of Eurasia and relies mostly on land-based connecting networks.